Bonuses, profit-sharing and job satisfaction: The more, the better? - Marco Clemens (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
Managers frequently offer unconditional bonuses and profit-sharing payments to their employees. The isolated effects of the former payment type on job satisfaction, in particular, have received little empirical attention. This study uses German panel data and shows that, even when total income is held constant, workers report significantly higher levels of job satisfaction when wages contain such bonuses, mostly regardless of their relative size. Conversely, profit-sharing payments show a positive association only if they are sufficiently large. However, when endogeneity issues are taken into account, the latter correlation becomes weaker or vanishes. The findings have significant implications for managers when designing salary packages since they imply that monetary gifts in the form of unconditional bonus payments can be a beneficial alternative to incentives in enhancing employee's job satisfaction.
Keywords: J33; M52; M54; I31; 330; bonuses; profit-sharing; gift-exchange; incentives; job satisfaction